Manajemen Sumber Daya pada Perguruan Tinggi Islam - Imaduddin (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2022)
This article discusses the importance of human resources in managing the resources available on earth. Humans were created by Allah to manage the earth and its resources for their own well-being, other creatures, and the entire universe. Therefore, these resources should be managed properly, as they are entrusted to humans and they will be held accountable for them in the hereafter. The management of human resources is crucial in organizations, corporations, and institutions, including universities. Human resource management is the lifeblood of institutions because the managed human factor determines the movement or stagnation of the institution's activities. The article presents various approaches, including political, economic, legal, socio-cultural, administrative, and technological, to demonstrate the strategic position of human resource management in university institutions. In conclusion, it emphasizes that a large capital or advanced technology is insufficient to build a successful institution, and it is the right management of human resources that matters most.